Piaget's developmental theory conversation [videorecording] - Karplus, Robert (Davidson Films, 1966)
Shows children in individual interviews when they are presented with tasks involving conservation of quantity, length, area, and volume using standard procedures developed by Swiss psychologist Jean Piaget.